ANALISIS KESALAHAN SISWA SEKOLAH MENENGAH PERTAMA PADA MATERI PECAHAN - Eyus _ Sudihartinih; Laila Maya Santi (Jurnal Pendidikan (Teori dan Praktik), 2019)
This research aims to analyze junior high school students error in solving mathematics test on fraction using Makhubele, Nkhoma, and Lunetas error category. This research was conducted by giving individual written test (three question) in the fraction material. Participants in this study were 5 junior high school students who had studied fraction material in their school. Based on the results of data analysis, it was concluded that students in number 1 had 2 students who did err1 (slip) and 1 student who did err2 (conceptual error), in number 2 there was 1 student who did err3 (procedural error), and in number 3 there is 1 person who did err2 and 1 person who did err1.